Pre- and post-COVID practice of interventional pulmonology in adults in Portugal - Guedes, F. (2022)
Funding Information: We thank Prime Focus for providing language help and writing assistance to this article. Publisher Copyright: © 2022 Sociedade Portuguesa de Pneumologia